Being nature - Ng, Pei Ling (2018)
Being Nature explores the intimate connection of nature, mindful observation and needlework. In today’s fast-paced society of Singapore stressful lifestyle, mindfulness helps to combat the automatic pilot mode of individuals by paying attention to what is salient in the present moment. The project aim is to explore the present moment through mindfulness, which helps to calm the mind and body to improve the overall balance of one’s well-being. Mindfulness in this project is the observation of nature that brings stillness through needlework. In addition, mindfulness is also the attention of the breath that flows in sync with the act of needling. The breath becomes an anchor to the present moment as one focus on the breathing instead of distracting thoughts.